False Measurement of Blood Amino Acids by LC-MS/MS in a Patient Dependent on Matrix Effect after Total Parenteral Nutrition Infusion - Guzelcicek, Ahmet; Gönel, Ataman; Demir, Abit; Koyuncu, Ismail (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background and Aim: Although it is widely known that the total parenteral nutrition (TPN) used frequently in intensive care units has unwanted side effects, there is little known about how it interferes with the amino acid levels taken during the diagnosis of metabolic diseases. Amino acid can lead to inaccurate measurements with mass spectrometry due to its high molecular content of lipids and carbohydrates, which modifies the blood matrix. The purpose of this study was to emphasize the results of amino acid interference, measured with mass spectrometry, in patients administered with TPN. Case Presentation: Incorrect clinical interpretation resulted in the case of a pneumonia patient with false positive and negative blood amino acid levels caused by TPN infusion. The amino acid profile had been requested to rule out an amino acid metabolic defect in the two-year-old boy who arrived at the pediatric clinic complaining of respiratory distress, tachypnea and hypoxemia. He was monitored in the intensive care unit for further investigation. The personnel who had performed phlebotomy also carried out the sampling during the TPN infusion administration. This caused the amino acid results and an incorrect interpretation. The following deviation ratios were detected: phenylalanine 102%, leucine 86%, isoleucine 106%, GABA 200%, citrulline 238%, glutamine 178%, ornithine 216%, 1- methyl-l-histidine 1471%, serine 312%, alanine 163%, glycine 355%, homocitrulline and carnosine 444%. The amino acid blood level measurements taken for diagnosis and screening in suspected metabolic disease may lead to involuntary false low or elevated results in patients administered with TPN. Conclusion: This case demonstrates that TPN solutions affect the reference method of mass spectrometry measurement methods due to the concentration of ingredients. We suggest that inaccurate results can be avoided by carrying out the sampling prior to TPN infusion in patients whose plasma amino acid levels will be measured.
Keywords: matrix effect